2019
DOI: 10.3389/fpsyg.2018.02715
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Effects of VLBW/PT Birth Status and Maternal Emotional Availability (EA) on Child EA Trajectories

Abstract: Few studies have examined the longitudinal impact of birth status on the infant–mother relationship and on children’s socio-emotional development. In the present study we investigated developmental patterns of such relationships [using the Emotional Availability (EA) Scales] in fullterm and VLBW/PT infants from infancy to emerging school age. Our objectives were to: (a) model the developmental trajectories of EA dimensions (maternal sensitivity, structuring, non-hostility; child responsiveness, involvement) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
(123 reference statements)
3
12
0
Order By: Relevance
“…18 Moreover, considerable literature suggests that supportive and structured parenting is associated with improved neurodevelopmental and behavioral outcomes in children born very preterm 19,20 ; however, few longitudinal studies have investigated long-term benefits. 6,21,22 In an earlier cohort, 9 we found that sensitive and warm (nonhostile) parent interactions partially ameliorated the negative association of neonatal painrelated stress on internalizing behaviors at age 1.5 years, whereas parenting stress was associated with greater prevalence of these behaviors. It is unknown whether a supportive parenting environment (parenting stress and parent behavior) attenuates the association between neonatal pain-related stress and child internalizing behaviors beyond 1.5 years.…”
Section: Introductionmentioning
confidence: 75%
“…18 Moreover, considerable literature suggests that supportive and structured parenting is associated with improved neurodevelopmental and behavioral outcomes in children born very preterm 19,20 ; however, few longitudinal studies have investigated long-term benefits. 6,21,22 In an earlier cohort, 9 we found that sensitive and warm (nonhostile) parent interactions partially ameliorated the negative association of neonatal painrelated stress on internalizing behaviors at age 1.5 years, whereas parenting stress was associated with greater prevalence of these behaviors. It is unknown whether a supportive parenting environment (parenting stress and parent behavior) attenuates the association between neonatal pain-related stress and child internalizing behaviors beyond 1.5 years.…”
Section: Introductionmentioning
confidence: 75%
“…Because the EA-Z were not available with the 2nd edition of the EA Scales, we did not have information on "emotional attachment" of these children using the EA-Z. Findings from Salvatori et al (2016) echo the Stack et al (2019) findings in that when the mothers' EA improved between 18 and 30 months, the child's EA also improved over this time period. However, what was clear in the Salvatori et al (2016) study was that the EA-Z were lowest in the extremely low birth weight (ELBW) group compared to the VLBW and control groups (note that the weight of the VLBW is slightly higher than that of the ELBW), whereas Human Development 2022;66:192-215 DOI: 10.1159/000525256 they were not able to pick up these EA issues in any of the individual dimensions.…”
Section: Typically Developing Children Experiencing Physical Vulnerab...mentioning
confidence: 96%
“…Very Low Birth Weight/Prematurity. To our knowledge, the study by Stack et al (2019) is not the first study of EA in families with a child with very low birth weight (VLBW) or prematurity, but they are the first to follow these children over time, in line with the clear increase in the use of EA in longitudinal work. Stack et al (2019) conducted a 4-wave longitudinal (child age 6, 12, 18, and 57 months) of infants born with VLBW (VLBW and preterm [PT], defined as 800-1,500 g, corrected for gestational age).…”
Section: Typically Developing Children Experiencing Physical Vulnerab...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, evolutionary frailties in preterm infants may impair their ability to express emotional states, including crying, making it difficult for mothers to attune to their child's needs. Several studies have associated preterm birth with altered maternal behaviours [21][22][23][24][25][26]. Mothers of preterm infants are likely to touch, smile at, and speak to their babies much less frequently than mothers of full-term babies [22,27].…”
Section: Introductionmentioning
confidence: 99%